THU0245 Relative risk chart score for the assessment of the cardiovascular risk in young patients with ankylosing spondylitis. (12th June 2018) - Atienza-Mateo, B.; Martín-Varillas, J.L.; Domínguez-Casas, L.C.; Vegas-Revenga, N.; Rueda-Gotor, J.; Genre, F.; Corrales, A.; Blanco, R.; Fuentevilla, P.; Portilla, V.; Expósito, R.; Mata, C.; et al.
Abstract : Background: Ankylosing spondylitis (AS) is associated with increased rates of cardiovascular (CV) mortality. CV events can be prevented by identifying patients with high CV risk who can beneficiate from strict primary prevention measures. The systematic coronary risk evaluation (SCORE) is the predictive model recommended in Europe, but it underestimates the CV risk in individuals under 50 years old. Objectives: To determine if the use of the relative risk (RR) chart score (figure 1) may help to identify young AS patients at high risk of CV disease. Methods: A set of 73 AS patients younger than 50 years old without history of CV events, diabetes mellitus or chronic kidney disease was assessed. CV risk was calculated according to the total cholesterol systematic coronary risk evaluation (TC-SCORE) and the RR chart score. A value of C-reactive protein (CRP) >3 mg/L at diagnosis, cut-off point associated with an increased risk of CV events, and carotid ultrasound data performed at the time of the assessment were also analysed. Results: Twenty (27.4%) of 73 patients exhibited carotid plaques and, consequently, they were classified into the category of very high CV risk. CRP>3 mg/L at disease diagnosis was associated with the presence of carotid plaques after adjustment for confounding factors (odds ratio 5.66, 95% confidence interval 1.11–28.77; p=0.03). None of these young patients were included in the category of high/very high CV according to the TC-SCORE. Whereas only 5 (14.2%) of the 35 patients with RR=1 had carotid plaques, 15 (39.5%) of 38 with RR >1 showed plaques. A model that included the performance of carotid US in patients with RR >1 who had CRP>3 mg/L at disease diagnosis allowed us to identify 60% of young AS with very high CV risk, with a specificity of 77.4% (area under the curve [AUC]: 0.69). The performance of carotid US in young AS patients with RR >1 regardless of CRP data at diagnosis increased the sensitivity up to 75% at the expense of a significant decline in the specificity to 56.6% (AUC: 0.66) (table 1). The gold standard used to define high/very high cardiovascular risk was the presence of TC-SCORE ≥5% or carotid plaques. Conclusions: RR chart score assessment may help to identify young AS at high risk who are underdiagnosed as having very high CV risk by the SCORE. Disclosure of Interest: None declared